(untitled) (Geography and Tourism, 2019)
The article discusses the potential and perspectives of geotourist functions development in three selected communes of the Lower Silesian Voivodship (Świerzawa, Ząbkowice Śląskie, Stronie Śląskie). These regions already possess a number of geotourist objects which attract tourist traffic, and whose presence creates further prospects for the development of tourism in this direction. Based on the conducted indoor studies and field reconnaissance, the author proposed and analysed prospective geostations, which may create a coherent network of objects, and thus, increase the development potential of this particular form of tourism. The presented assessment was predicated on a point-based evaluation method utilizing predetermined criteria for geostation valorisation. At the same time, the article draws attention to the difficulties pertaining to straightforward synthetic interpretation of the value assessment of individual structures. It is also shown that the existing nationwide database of geosites proves to be lacking in terms of both the potential assessment as well as the needs for planning of geotourism development at a local level.